"Meat Seasoned with Divine Wrath"? The Quails Tradition(s). Issue 1 (2nd January 2021) - Robinson, Bernard P.
ABSTRACT: We find quails accounts in Exod 16 (P) (cf Ps 105) and Num 11 (non-P) (cf Pss 78 and 106). In the Pentateuch as it stands, they narrate two separate events. In both, the quails are a divine gift, but in Num 11 their arrival follows an excessive murmuring. The people then scurry to amass huge quantities of quails per person, and it is this action that leads YHWH to inflict a lethal blow on them as soon as they begin eating. The meat itself (distributed probably by the seventy elders in the role of šōṭerîm ) is not harmful; it is not "meat seasoned with divine wrath", pace C.H.Spurgeon. Num 11 is a narrative calculated to discourage greed and unjustified murmuring.